2013
DOI: 10.1257/aer.103.2.585
|View full text |Cite
|
Sign up to set email alerts
|

Designing Random Allocation Mechanisms: Theory and Applications

Abstract: Randomization is commonplace in everyday resource allocation. We generalize the theory of randomized assignment to accommodate multi-unit allocations and various real-world constraints, such as group-specific quotas ("controlled choice") in school choice and house allocation, and scheduling and curriculum constraints in course allocation. We develop new mechanisms that are ex-ante efficient and fair in these environments, and that incorporate certain non-additive substitutable preferences. We also develop a "u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
251
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(264 citation statements)
references
References 44 publications
0
251
0
Order By: Relevance
“…More precisely, one would express the original assignment probabilities as a convex combination of such constrained deterministic assignments. This idea has been previously explored in Budish et al (2013). However, by the above argument, one would expect gains in diversity to be small.…”
Section: Ec4 Detailed Analysis With Two Schoolsmentioning
confidence: 95%
See 1 more Smart Citation
“…More precisely, one would express the original assignment probabilities as a convex combination of such constrained deterministic assignments. This idea has been previously explored in Budish et al (2013). However, by the above argument, one would expect gains in diversity to be small.…”
Section: Ec4 Detailed Analysis With Two Schoolsmentioning
confidence: 95%
“…Our approach of defining a mechanism by implementing the marginal assignment probabilities is similar to Budish et al (2013). They study a more general framework and address the issues of group-specific quotas, ex-ante efficiency, ex-post fairness, and implementability of lotteries under general constraints.…”
Section: Related Workmentioning
confidence: 99%
“…One of the most fundamental and ubiquitous problems in microeconomics and operations research is how to assign objects to agents based on their individual preferences (see, e.g., [21,4,5]). In its simplest form, the problem is known as the assignment problem, the house allocation problem, or two-sided matching with one-sided preferences.…”
Section: Introductionmentioning
confidence: 99%
“…Taking cue from this observation, McCutchen [17] proposed two quantities-the unpopularity margin and the unpopularity factor -to measure the unpopularity of an assignment and defined the notion of a least unpopular assignment, which is guaranteed to exist. 5 However, computing least unpopular assignments turned out to be NP-hard. Alternatively, Kavitha et al [13] suggested the notion of popular random assignments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation